2004
DOI: 10.1002/adsc.200404067
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Synthesis of Secondary Alcohols using Triphenylborane

Abstract: Dedicated to Joe P. Richmond on the occasion of his 60 th birthday.Abstract: Asymmetric phenyl transfer reactions with triphenylborane as aryl source and a ferrocene-based catalyst give secondary alcohols in high yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 54 publications
0
21
0
1
Order By: Relevance
“…Braga demonstrated that the acceleration could be achieved by microwave irradiation 53. Based on Bolm's breakthrough, several aryl boron derivatives, such as triarylboranes42,43,49,54-57 and boroxines,52,58,59 were successfully employed in the asymmetric arylation of aldehydes. It is noteworthy that highly enantioselective late transition metal-based catalysts can also be employed with boronic acid derivatives 60-62…”
Section: Introductionmentioning
confidence: 99%
“…Braga demonstrated that the acceleration could be achieved by microwave irradiation 53. Based on Bolm's breakthrough, several aryl boron derivatives, such as triarylboranes42,43,49,54-57 and boroxines,52,58,59 were successfully employed in the asymmetric arylation of aldehydes. It is noteworthy that highly enantioselective late transition metal-based catalysts can also be employed with boronic acid derivatives 60-62…”
Section: Introductionmentioning
confidence: 99%
“…Triarylboranes 5 and triarylalanes 6 have been also employed in enantioselective additions to both alkyl and aryl aldehydes with reasonable success. However, these reagents are not readily available, they deliver only a single aryl group, and they are pyrophoric, greatly diminishing their appeal.…”
Section: Introductionmentioning
confidence: 99%
“…Bolm et al reported that the asymmetric phenyl transfer reaction proceeds with an inexpensive triphenylborane as aryl source in the presence of chiral ferrocene based catalyst 65 (Table 17) [117]. In this method, a long preparation period in the boron-to-zinc exchange reaction is unnecessary, although excess amounts of a Ph-source and Zn-source are required.…”
Section: 5enantioselective Arylation To Aldehydesmentioning
confidence: 98%